The role of artificial intelligence in contemporary literary practice: Perceptions and implications - Firah Alifiah Ningrum; Yeti Mulyati; Sumiyadi Sumiyadi; Halimah Halimah; Zhuoxun Ye (NOTION: Journal of Linguistics, Literature, and Culture, 2026)
This study examines the relationship between literature and Artificial Intelligence (AI) in the development of digital technology. While AI is increasingly shaping how writers work from generating ideas to editing, there is still a lack of empirical focus on how this affects authorial agency, especially in the Indonesian context. This study used a qualitative descriptive method, distributing an online questionnaire to 53 literary writers in Indonesia, including poetry, short story, novel, and drama writers. The results showed that 62% of respondents use AI as a tool to facilitate the writing process, while 22% view it as a potential threat to creativity. Most respondents (82%) believe that AI cannot replace writers because it lacks emotional experience and cultural understanding. Furthermore, 50% of respondents believe AI can improve the technical aspects of writing, although 22% stated that excessive use can diminish the originality of the work. These findings imply that the integration of AI requires writers to develop critical digital literacy, ensuring that technology serves as a collaborative partner rather than a replacement for human creative identity. Overall, this study concludes that AI plays a supporting role in the creative process but still requires the writer’s supervision and control to maintain the quality and originality of literary works. Beyond individual practice, these results highlight the need for literary institutions to establish ethical guidelines that protect authorial voice in an increasingly automated environment.